PENDUGAAN PARAMETER DAN ELASTISITAS PENAWARAN JAGUNG DI PROVINSI JAWA TIMUR - Napitupulu, Tia Sofiani; Sumarlina, Sumarlina (Universitas Galuh, 2023)
Corn (Zea mays L.) is one of the main food crops in Indonesia and globally. Currently, corn has developed into functional food ingredients, emergency food ingredients, and industrial raw materials in the form of various products. This resulted in an increase in the national corn productivity rate with East Java as the province contributing the highest corn production in the latest report (2020). Therefore, this study aims to determine the development of corn supply, analyze the factors that influence corn supply and analyze the elasticity of corn supply in East Java Province. This study uses time series data for 2011-2021. The estimation of the parameters of the corn supply equation is conducted using multiple linear regression analysis with the OLS (Ordinary Least Squares) method. The findings from this study include: (1) the development of corn supply in East Java fluctuated but tended to increase; (2) the variables of price, harvested area, and corn production in the previous year had a significant effect on corn supply; and (3) the land area is elastic to supply in the short term, while in the long run, only price changes are responsive to supply.